2017
DOI: 10.22159/ajpcr.2017.v10i10.19138
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study of Pterion and Its Clinical Significance

Abstract: Objective: Pterion is an area formed by the union of frontal, parietal, temporal, and sphenoid bones. It exhibits variations in the sutural pattern of fusion of constituent bones. Basing on this, the pterion can be classified into four varieties. According to Murphy, these are sphenoparietal, frontotemporal, stellate, and epipteric. The anatomical location of the pterion is necessary for the surgical management of extradural hemorrhage, aneurysm, and brain tumors located in the anterior and middle cranial foss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…This approach has more advantages than the traditional surgical approach with minor tissue damage, less brain retraction, a superior cosmetic results and a shorter duration of surgery ( 6 ). Fundamentally, the knowledge of the pterion sutural patterns and its relationship to the bony landmarks is useful for specialist in various field of medical professions particularly for neurosurgeons ( 17 , 18 ). The main findings of this study are notably the higher occurrence of the sphenoparietal type of pterion with the absence of frontotemporal type.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has more advantages than the traditional surgical approach with minor tissue damage, less brain retraction, a superior cosmetic results and a shorter duration of surgery ( 6 ). Fundamentally, the knowledge of the pterion sutural patterns and its relationship to the bony landmarks is useful for specialist in various field of medical professions particularly for neurosurgeons ( 17 , 18 ). The main findings of this study are notably the higher occurrence of the sphenoparietal type of pterion with the absence of frontotemporal type.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, epipterical type was the least observed type (Type C). In order to locate the pterion, different landmarks have been described in the literature, such as arcus zygomaticus or frontozygomatic suture (2,7). In the present study, palpable landmarks under the surface of the skin without any further skin incision were chosen to locate the pterion, such as tuberculum marginale and processus mastoideus.…”
Section: Discussionmentioning
confidence: 99%
“…The problem in developing these systems is really to maintain the release of the drug and moreover extending the residence of dosage forms in the stomach till the drug is completely delivered at the required time [3]. Extended stomach residency improves bioavailability while prolonging the drug release and reducing drug wasting [4,5]. Extended stomach residency of dosage forms has pharmacokinetic benefits, such as the stability of therapeutic levels throughout a long time subsequently, a decrease in therapeutic level fluctuations.…”
Section: Introductionmentioning
confidence: 99%